ISLAMIC HOMESCHOOLING UPAYA MEMBANGUN PENDIDIKAN KARAKTER ISLAMI (Studi Kasus di Islamic Homeschooling Fatanugraha Wonosobo) - Maryono Maryono (IAIN Ponorogo, 2013)
Home schooling is the education model in which the family decides to take their own responsibility for the education of children using the premises as a home base education. Nowadays, homeschooling becomes a viable alternative option for particular group of society as they realize that the actual pattern of formal education in Indonesia has not touched yet the substance of the real needs of globalization challenges that must be addressed positively by learners to prepare the required competence they should have in accordance with their future job. There are some supporting factors that contribute to the implementation of homeschooling education in building Islamic character education, such as high motivation in learning, sincerity of teachers, parent support and adequate learning facilities. Conversely, there are some factors that might be hindered, such as the public scorn, less conducive place, and less favored by regular schools.المدرسة الأسرية هي طراز من التربية حيث أن الأسرة اختارت أن تتولى مسؤولية تربية الأبناء بنفسها ويكون البيت مركزا لها. وتكون المدرسة الأسرية الآن موضع اختيار للمجتمع حين وعى المجتمع أن طراز التربية الرسمية في إندونيسيا لم يلمس الحاجة الأساسية للتحديات في عصر العولمة الذي لابد أن يقابله الطلاب إيجابيا لإعداد الخريجين الأكفاء المناسب بحاجاتهم في ممارسة أنشطتهم وأعمالهم. وهناك مؤيدات لها اسهام في تطبيق المدرسة الأسرية لبناء السلوك الإسلامي، منها: الرغبة في التعلم عالية، المدرسون المخلصون، المؤيدات من أولياء الطلاب، ووسائل التعليم الكافية. أما العوائق فيها : الاهمال من المجتمع، موضع الدراسة غير لائق، والكره من المدارس الرسمية.